Photoswitchable Norbornadiene-Quadricyclane Interconversion Mediated by Covalently Linked C-60 - Lorenz, Patrick; Hirsch, Andreas (Chemistry - A European Journal, 2020)
The synthesis and properties of various norbornadiene/quadricyclane (NBD/QC) fullerene hybrids are reported. By cyclopropanation of C-60 with malonates carrying the NBD scaffold a small library of NBD-fullerene monoadducts and NBD-fullerene hexakisadducts was established. The substitution pattern of the NBD scaffold, as well as the electron affinity of the fullerene core within these hybrid systems, has a pronounced impact on the properties of the corresponding energy rich QC derivatives. Based on this, the first direct photoisomerization of NBD-fullerene hybrids to their QC derivatives was achieved. Furthermore, it was possible to use the redox-active fullerene core of a QC-fullerene monoadduct to enable the back reaction to form the corresponding NBD-fullerene monoadduct. Combining these two processes enables switching between NBD and QC simply by changing the irradiation wavelength between 310 and 400 nm. Therefore, turning this usually photo/thermal switch into a pure photoswitch. This not only simplifies the investigation of the underlying processes of the NBD-QC interconversion within the system, but also renders such hybrids interesting for applications as molecular switches.
CRIS-Team WoS Importer:2020-03-06